Second Uterine Curettage and the Number of Chemotherapy Courses in Postmolar Gestational Trophoblastic Neoplasia: A Randomized Controlled Trial. Issue 5 (May 2019) - Hemida, Reda; Vos, Elvira L.; El-Deek, Basem; Arafa, Mohammad; Toson, Eman; Burger, Curt W.; van Doorn, Helena C.
Abstract : OBJECTIVE: To investigate the effect of second uterine curettage on the number of chemotherapy courses and relapse rate in low-risk postmolar gestational trophoblastic neoplasia. METHODS: In a phase III trial, patients with low risk gestational trophoblastic neoplasia were randomised (1:1) to a second curettage or no curettage group before methotrexate treatment. Eligibility criteria were serum human chorionic gonadotropin (hCG) level 5, 000 international units/L or less and fit for treatment with methotrexate. Exclusion criteria were previous uterine perforation and life-threatening bleeding. With a two-sided 5% significance level and a power of 99%, a sample size of 44 patients per group was necessary to detect a mean reduction in 2.3 chemotherapy courses. The primary outcome was the number of chemotherapy courses required for hCG normalization. Secondary outcomes were needed for second-line treatment, toxicity, relapse rates, and variables associated with number of chemotherapy courses. RESULTS: From October 2011 through February 2016, 89 patients entered the study at the Mansoura Trophoblastic Clinic; in each group, 43 patients were included in the intention‐to‐treat analyses. Surgical complications did not occur. The mean number of chemotherapy courses required to reach hCG normalization was 4.4±2.2 SD in the control group vs 3.8±2.3 SD in the intervention group ( P =.14). Groups were comparable in terms of second-line treatment needed to reach hCG normalization, and relapse within the first year. Only hCG levels related to the number of chemotherapy cycles required for hCG normalization. CONCLUSION: Second uterine curettage did not reduce the number of chemotherapy courses required or affect relapse rate in patients with low-risk postmolar gestational trophoblastic neoplasia. CLINICAL TRIALS REGISTRATION: Dutch Trial Registry, NTR3390. Abstract : Second uterine curettage has no effect on the number of chemotherapy courses or on the rate of relapse in low-risk postmolar gestational trophoblastic neoplasia.